Desencanto - Minei, André Teodoro [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
A journey from bits to affections, /desencanto (disenchantment) starts as agitation. It's a project that has a critique to utilitarianism in Design as its starting point, but tries to go further, pointing to the direction of an aesthetic (prone to experience), hybrid, potent, open, emergent Design; for the designing of connections, of means rather than ends. Connections to possible endings, or non-endings alike. The actualization (materialization) of the project takes place through interactive installations regarding themes such as movement, bodies and time. At its core are the search and offering of inspiration, contemplation and the comprehension of affections - of the world, of the other, and mainly, of oneself

Uma jornada dos bits aos afetos, /desencanto nasce de uma inquietação. Um projeto que tem como ponto de partida uma crítica ao utilitarismo no Design, mas procura ir além, apontando a um Design estético (experienciável), híbrido, potente, aberto, emergente; por um projetar não dos fins, mas das conexões para fins possíveis, ou mesmo não-fins. Sua atualização (materialização) se dá em instalações interativas, abordando temas como movimento, corpos e tempo. Em seu centro estão a busca e oferta de inspiração, contemplação e conhecimento dos afetos - do mundo, do outro e, principalmente, de si
Keywords: Desenho industrial; Utilitarismo; Interação social